Pharmacology of mitochondria - Singh, Harpreet (Associate Professor); Sheu, Shey-shing (Springer, 2017)
"This special book is conceived to highlight mitochondrial structural and functional integrity and how they are associated with several human diseases such as cardiovascular, cancer, renal, neurological disorder, and genetic disorders. The chapters contributed by leading mitochondrial researchers in the handbook will take us through the novel pharmacological strategies via mitochondria to understand their physiological and pathological role as well as present them as therapeutic targets"--Publisher's description.
Keywords: Mitochondria.; Mitochondria -- Metabolism.; elektronické knihy; electronic books